Global extraction of the parton-to-pion fragmentation functions at NLO accuracy in QCD - Hernández-Pinto, R.J. (2016)
In this review, we discuss the results on the parton-to-pion fragmentation functions obtained in a combined NLO fit to data of single-inclusive hadron production in electron-positron annihilation, proton-proton collisions, and lepton-nucleon deep-inelastic scattering. A more complete discussion can be found in Ref. [1].